Islamic Financial Innovation in Agriculture, Facilitate Farmer Access to Obtain Food Production Financing - Khasanah, Umrotul; ., . (International Journal of Engineering and Technology, 2019)
The study focuses on’’ The Islamic Financial Innovation at Farmers Community ’’. This study aims to: (1) exposing farmers’ perceptions of the barriers get operational financing agricultural production, (2) what can do the farmerstoward Islamic Financial Innovation, (3) The views of farmers on Islamic financial innovation. This study ultimately produces research findings. First, various obstacles farmers got operational financing access of agricultural production. Second, there were two models of Islamic finance practiced by the farmers: Profit Sharing Model (SBH) SBH One per three and one per two. Third, Islamic finance innovation facilitate farmers to get financial access. Â Â